Kajian Arsitektur Organik Wisata Kuliner Kabupaten Bandung Jawa Barat - Lia Amelia Megawati (Jurnal Pelita Teknologi, 2019)
The high demands for recreational places in several major cities in Indonesia is an opportunity for activists of recreational businesses to provide tourist locations that are able to increase the profit coffers. Tourism that will be discussed in this article is culinary tourism. Culinary itself is a processed product in the form of cuisine, the dishes are in the form of side dishes, food and drinks. Culinary is everything related to food and food ranging from raw materials to processing and presentation. The visitors will be presented with several recreational facilities with a variety of typical traditional food and drinks in their respective regions. Organic architecture describes the relationship with nature as a whole and the parts that have ties to their natural conditions. Organic architecture itself is based on natural behavioral factors, symmetrical patterns and firm lines, as well as natural life. Basically, organic architecture is architecture that is based on nature. This article presents a brief study of the application of organic architecture to several culinary attractions located in Bandung Regency, West Java.